Pemanfaatan Gas Amonia Limbah Ternak Sapi untuk Produksi Pupuk Cair Amonium Sulfat pada Usaha Tani Sejahtera - Mochammad Agung Indra Iswara; Ulfiana Ihda Afifa; Diana Rachmawati; Ariani Ariani; Ari Susanti; Arif Rahman Hakim (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service program aims to utilize ammonia gas generated from cow manure waste as a raw material for producing liquid ammonium sulfate fertilizer at UMKM Usaha Tani Sejahtera, Duwet Village, Tumpang District, Malang Regency. The main problem faced by the partner community is the emission of ammonia gas produced during the fermentation of solid organic fertilizer, which has not been properly utilized and causes air pollution. The program provides a solution through technical training and demonstrations of converting ammonia gas by reacting it with sulfuric acid to produce liquid ammonium sulfate fertilizer (ZA). The activities included lectures, interactive discussions, and hands-on practice using a fermentor equipped with a gas absorption system. A participatory approach was implemented to enhance the partner’s knowledge, skills, and awareness of environmentally friendly waste management. The results indicated improved participants’ understanding of the ammonia-to-fertilizer conversion process and the implementation of circular agriculture principles. Participants were able to operate the fermentor independently and produce high-quality liquid fertilizer. This program contributes to reducing air pollution, increasing the economic value of livestock waste, and promoting the zero-waste farming concept to support sustainable agriculture at the UMKM level.